ANALISIS PENGARUH UKURAN PERUSAHAAN, LAVERAGE, KEPEMILIKAN INSTITUSIONAL, DAN KEPEMILIKAN MANAJERIAL TERHADAP MANAJEMEN LABA - Kusumawardana, Yogi; Haryanto, Mulyo (Diponegoro Journal of Management, 2019)
The existence of information asymmetry and the tendency of external parties (investors) to pay more attention to profit information as a parameter of corporate performance, encouraging management to perform earnings on firm size, laverage, institutional ownership, and managerial ownership.The research was conducted to analyse the effect of firm size, laverage, institutional ownership and managerial ownership as independent variable to earnings management as dependent variable either partially or simultaneously. This study uses Discretionary Accruals as a profit management proxy calculated using a modified jones model. Sampling method used in this research is purposive sampling. The sample used is 20 manufacturing companies for the 2012-2015 observation year. So as many as 80 samples of observational research. Sources of research data obtained from the financial statements of manufacturing companies in Indonesia are listed in Panama Paper.Based on the results of the calculation of the classical assumption test is known that the data used in this study normal distribution, can not multikolonieritas, free autocorrelation and free heterokedastisitas. Of the four hypotheses proposed, only firm size significantly affects earning management, while leverage, institutional ownership, and managerial ownership have no significant effect on earnings management. For futher research it is expected to use other variables that influence earnings management in addition to the variables that have been used in this study, prolong the observation time, and increase the number of samples with the expectation of synchronization between partial hypothesis and simultaneous hypothesis.